A systematic literature review on downlink frames in LoRaWAN. (July 2022) - Jebril, Akram H.; Rashid, Rozeha A.
Highlights: Downlink frames information of LoRaWAN is used for systematic research analysis. PRISMA Mechanism is addressed in evaluation of performance metrics. Data extraction and synthesis is found by systematic review process. Abstract: LoRaWAN is one of the technologies in the Low Power Wide Area Network (LPWAN) which has gained considerable attention of the research community over the last few years, especially in the IoT applications. It provides low power and high data throughput across the wide range of coverage areas. LoRaWAN communication is established through transmission of frames either on uplink or downlink. In this study, a systematic review of the leading-edge work of LoRaWAN communication through downlink has been presented. The systematic review process follows the PRISMA Mechanism in which the research analysis has been taken from the time period between 2016 and 2021. In this context, various LoRaWAN architecture models have been compared through their performance metrics like throughput, data rate, packet delivery ratio, delay or latency, etc. and their performance are also evaluated. Graphical abstract: Image, graphical abstract